Pengaruh Site Characteristics terhadap e-WOM melalui Customer Satisfaction, e-trust dan e-commitment PADA PENGGUNA APLIKASI situs belanja online “Tokopedia” (Studi kasus Tangerang Raya) - Susiati, Asriani; Puspitasari, Ria (Universitas Muhammadiyah Tangerang, 2022)
AbstractThe purpose of this paper is to highlight the positif significance of site characteristics (shopping convenience, site design, informativeness, security and communication) with e-WOM mediated customer satisfaction, e-trust and e-commitment. The objectives of this research was : (a) the positive effect of shopping convenience to customer satisfaction, (b) the positive effect of site design to customer satisfaction, (c) the positive effect of informativeness to customer satisfaction, (d) the positive effect of security to customer satisfaction, (e) the positive effect of communication to customer satisfaction, (f) the positive effect of customer satisfaction to e-trust, (g) the positive effect of customer satisfaction to e-commitment, (h) the positive effect of e-trust to e-commitment. (i) the positive effect of e-trust to e-word of mouth, (i) the positive effect of e-commitment to word of mouth. The design of this research applies a survey toward unit of analysis on Application Tokopedia to interview the customers for testing hypothesis. Meanwhile the required data consist of nine variables; shopping convenience, site design, informativeness, security, communication, customer satisfaction, e-trust, e-commitment and e-word of mouth. The aggregate numbers of customer being respondent of the study are 180. Data analysis used in this research was consists Structutal Equation Modelling (SEM) of Path Method by AMOS 7.0 as software. The result of this research conclude that variable of shopping convenience, site design, informativeness, security and communication attributehad a positive effect to customer satisfaction, and variable customer satisfaction had positive effect to e-trust and had negative effect to e-commitment, and than variable e-trust had negative effect to e-WOM but e-commitment had positive effect to e-WOM.Keywords: customer satisfaction; e- commitment, e-trust; and e-WOM.